Multiscale computational fluid dynamics applied to buoyancy-driven flows - Zuñiga, Santiago L. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2025)
Fil. Zuñiga, Santiago L.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina